The effect of the listening triangle strategy on cognitive organization and the performance and accuracy of some basic football skills - Hazaa , Fareek (Journal of Physical Education, 2024)
This study aims to build a scale of cognitive organization in football, prepare educational exercises with football in the strategy of listening to students, identifying the impact of the strategy of listening triangle in cognitive organization and the performance of the extinguishing skills of the sole of the foot and the extinguishing of the chest and the accuracy of the skill of the football for students, and I adopt the method of experimental research By designing the experimental and controlled groups, the community’s limits were for fifth -grade middle school students in the morning study at Al -Fursan High School for Boys for the academic year (2023/2024) of the total number of (166) students, all of whom were deliberately chosen in a comprehensive inventory by (100%), were chosen (10 Rangeous students of the exploratory sample at (6.024 %) of the origin society, and (100) students were chosen to build the cognitive regulation scale in football, and they represent (60.241 %) of the origin society, and the remaining (56) students from two divisions to represent the application sample in proportion (33.735 %) of the origin community, according to the design requirements, two random divisions were chosen, so that the 28 students were chosen, and the control reached (28) students, The scale of cognitive regulation in football was built by adopting systematic steps and statistical treatments, preparing educational exercises in the seat strategy, and applying them to students of the experimental group for a period of (12) weeks by (1) lesson a week and for each skill (4) lessons, and the period of time for research procedures has reached From the date (4/10/2023) to the date (12/28/2023), and after the end of the experiment, the results were addressed with the system (SPSS) to be the most important conclusions and recommendations that the scale of cognitive organization in football is suitable And it enjoys the foundations and scientific transactions for its transmission, and the employment of educational exercises in the strategy of listening triangle to perform the extinguishing skills of the sole of the foot and the burning of the chest and the accuracy of the skill of the handling of football in practical lessons is suitable Performing my outside ring skills with the soles of foot, chest extinguishing, and the accuracy of the skill of handling football for students who study it, And by superiority over their peers who study without them, it is necessary to focus on practice and repetition in improving the performance of the extinguishing skills of the sole of the foot and infection in the chest and the accuracy of the skill of the handling football in the middle of the good employment of the listening triangle in teaching and not to exaggerate the explanations to support the cognitive structure of the performance of performance and its accuracy in football.